2021
DOI: 10.1021/acs.jchemed.1c00416
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Success through Undergraduate Research Experience in a Historically Black College and University

Abstract: This reflective overview describes the benefits of participation in authentic undergraduate research for students at a Historically Black College and University (HBCU). The department of chemistry and biochemistry at Hampton University has an undergraduate research environment that empowers and fosters a success-oriented research experience for our diverse students. By engaging undergraduate students in research early in their careers, we successfully motivate students to make informed decisions about pursuing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Similarly, Ghebreyessus et al. (2021) reported that an “authentic undergraduate research” experience for students at a Historically Black College and University (HBCU) includes an inclusive environment that cultivates a sense of belonging, recognizes the talent of all students, and fosters nurturing and culturally responsive faculty support systems. These studies, among others, suggested that the mere availability of HIPs is not enough.…”
Section: Culturally Engaging Campus Environments (Cece) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ghebreyessus et al. (2021) reported that an “authentic undergraduate research” experience for students at a Historically Black College and University (HBCU) includes an inclusive environment that cultivates a sense of belonging, recognizes the talent of all students, and fosters nurturing and culturally responsive faculty support systems. These studies, among others, suggested that the mere availability of HIPs is not enough.…”
Section: Culturally Engaging Campus Environments (Cece) Modelmentioning
confidence: 99%
“…In another example, Malotky et al (2020) reported on a communitycollaborative research program in which undergraduates engage with culturally familiar communities and learn culturally relevant pedagogies that teach them how to participate in a diverse society and foster a sense of belonging, equity, and justice. Similarly, Ghebreyessus et al (2021) reported that an "authentic undergraduate research" experience for students at a Historically Black College and University (HBCU) includes an inclusive environment that cultivates a sense of belonging, recognizes the talent of all students, and fosters nurturing and culturally responsive faculty support systems. These studies, among others, suggested that the mere availability of HIPs is not enough.…”
Section: Culturally Engaging Campus Environments (Cece) Modelmentioning
confidence: 99%
“…CUREs represent an approach for increasing access for undergraduate students’ participation in research, providing an alternative to the more typical mentored undergraduate research experiences (UREs) in which individual faculty members mentor undergraduate students within their laboratories. Additional approaches for more broadly engaging undergraduate students with research include precollege summer workshop programs, research-group-based undergraduate research, , summer undergraduate research experiences, or combining CUREs with UREs . With the focus on incorporating research into a course, CUREs specifically provide students the opportunity to engage in research as part of the curriculum rather than conducting research as an independent study or as an extra-curricular activitywhich offers the advantage of increasing access to research opportunities for a larger number of students compared to mentored UREs; this is particularly valuable, because many students, particularly from underrepresented backgrounds, may not seek a mentored URE due to unfamiliarity with the work of scientists. , Furthermore, CUREs can broaden access to research for students who may not have the confidence, time, or resources to conduct often unpaid research in an academic laboratory. , CUREs also address the challenge of departments often not having enough faculty members available to mentor the number of undergraduate students within a given degree program. , By engaging more students in authentic research, CUREs represent the possibility of broadening the reported benefits for participating in UREs, which include improvements in learning, retention, and entry into the STEM workforce. , Notably, several studies indicate the wide range of benefits in these areas within the context of CUREs specifically, including benefits such as increases in self-efficacy, sense of belonging, and motivation. , …”
Section: Introductionmentioning
confidence: 99%
“…Due to the multitude of benefits associated with CUREs, a large number of new and innovative CURE projects have been published in the Journal of Chemical Education covering a variety of topics in analytical, organic, physical and biochemistry. , These previously published CURE programs not only demonstrated the feasibility of implementing undergraduate research experiences in a course setting with a much larger enrollment (some accommodate hundreds), but also validated that many of the aforementioned pedagogical benefits are well conserved in chemistry-based CURE programs. , Recently, Clark et al, Hauwiller et al, and Calvin et al, reported the expanding effort in experimenting CURE initiatives at the first-year level. ,, Together, they demonstrated the consistent and positive learning outcomes of CUREs for novice chemistry students, which promoted early career chemistry students to self-identify as chemists, and persist in the program. ,, Ghanem et al, further demonstrated that the implementation of CURE programs in chemistry education, through the full integration of training in mandatory and accredited general chemistry programs with open-ended research experiences, produced unexpected but positive outcomes in undergraduate science curricula . Encouraged by all the reported benefits and practicality of CUREs, we would like to report our newest development and implementation of an interdisciplinary CURE course (from here on referred to as CURE CHEM111).…”
Section: Introductionmentioning
confidence: 99%